RANCANGAN MODEL LAYANAN BIMBINGAN KELOMPOK DENGAN METODE ROLE PLAYING DALAM MENGURANGI PERILAKU BULLYING PESERTA DIDIK DI SMKN 3 PADANG - Rezki Fadila; Rici Kardo; Fuaddillah Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the high number of bullying cases perpetrated by students at SMKN 3 Padang. These behaviors include teasing, calling parents names, pushing, and even physical and social violence. The purpose of this study is to describe the bullying behavior of students and to design a group guidance service model using the role-playing method to reduce this bullying behavior. This study uses a quantitative descriptive approach with a sample of 32 grade XII AKL students. The instrument used was a questionnaire, with data analysis techniques using percentages and narratives. The results showed that bullying behavior was in the "quite high" category at 34%. The researchers developed a service model in the form of a module that includes RPL and materials that can be used by BK teachers as a guide in implementing the role-playing method to reduce bullying behavior.